Evidence for a very thick Kaapvaal craton root: Implications for equilibrium fossil geotherms in the early continental lithosphere - Tomlinson, Emma (My University, 2022)
The presence of diamonds of Archaean age within the cratonic lithosphere is surprising because their formation implies a cool early mantle lithosphere despite the early Earth's hotter state. There remains a widely (albeit not exclusively) held concept that the prevailing geothermal gradient within Archaean cratons was not much different from today. This ‘Archaean paradox’ is supported by pressure and/or temperature (PT) estimates of potentially ancient diamond inclusion (DI) falling close to modern cratonic geotherms. Solutions to the paradox include more effective Archaean heat loss mechanisms (e.g. heat pipes), deeper lithospheric mantle roots or the early lithosphere forming in a disequilibrium state. Here we demonstrate the effects of a thermally evolving Earth on equilibrium geotherms within the Kaapvaal craton of South Africa. We modelled geotherms from the present-day conditions backward in time to 3.0 Ga at thermal equilibrium in the lithosphere by adjusting three dominant variables: (i) time-corrected crustal heat production; (ii) a secularly cooling mantle potential temperature ( ) in the underlying convecting mantle; and, for illustrative purposes, (iii) variable depth of the lithosphere-asthenosphere boundary (LAB) or variable heat flow at the LAB. Computed model geotherms were compared to DI PT data from the Kaapvaal craton, as well as PT conditions recorded in mantle xenoliths of variable age. It is demonstrated that equilibrium geotherms in the lithosphere cannot be reconciled with PT conditions recorded in Kaapvaal craton DI nor with those recorded in Proterozoic xenoliths if either the lithosphere has remained of constant thickness or held a constant basal heat flux since 3.0 Ga. Rather, provided that PT conditions recorded by DI from the Kaapvaal craton reflect equilibration along fossil ancient equilibrium geotherms, it is required that the early lithosphere was substantially thicker than what is preserved today. The inferred former thickness of Kaapvaal craton could have reached up to ∼350 km if the prevailing mantle at the time of diamond encapsulation was high and they are of Archaean age. If, however, the Archaean asthenosphere was more modest or if the diamonds formed later than the Archaean the inferred LAB depths are shallower (∼250-275 km), but still substantially deeper than at the present day. Although only the Kaapvaal craton has the necessary DI PT constraints for this exercise, the fundamental nature of radioactive heat production rate and mantle cooling mean that our findings could imply that Earth's continental lithosphere in general attained its maximal vertical extent early in the Archaean and that cratons have been variably eroded and weakened since that time.
PUBLISHED
Keywords: geotherms; diamonds; thermobarometry; craton; heat flow; continents